On the Deformations and Derivations of n-Ary Multiplicative Hom-Nambu-Lie Superalgebras - Baoling Guan; Liangyun Chen; Yao Ma (Advances in Mathematical Physics)
We introduce the relevant concepts of n-ary multiplicative Hom-Nambu-Lie superalgebras and construct three classes of n-ary multiplicative Hom-Nambu-Lie superalgebras. As a generalization of the notion of derivations for n-ary multiplicative Hom-Nambu-Lie algebras, we discuss the derivations of n-ary multiplicative Hom-Nambu-Lie superalgebras. In addition, the theory of one parameter formal deformation of n-ary multiplicative Hom-Nambu-Lie superalgebras is developed by choosing a suitable cohomology.